Urine mRNA to identify a novel pseudoexon causing dystrophinopathy - Antoury, Layal (Ann Clin Transl Neurol, 2019)
In muscular dystrophies, identification of pathogenic pseudoexons involves sequencing of the target gene cDNA derived from muscle mRNA. Here we use a urine “liquid biopsy,” droplet digital PCR, and sequencing of PCR products to identify a novel cryptic splice site in DMD intron 67 that causes dystrophinopathy. Pseudoexon inclusion is 35% in urine cells, 34% in urine extracellular RNA (exRNA), and 54% in muscle biopsy tissue, but absent in serum exRNA. Our results suggest that cryptic splice site use varies depending on the RNA source, and that urine RNA has the potential to substitute for muscle biopsies to identify DMD pseudoexons.